Fast and Efficient 18F‐Labeling by [18F]Fluorophenylazocarboxylic Esters. Issue 2 (11th December 2013) - Fehler, Stefanie K.; Maschauer, Simone; Höfling, Sarah B.; Bartuschat, Amelie L.; Tschammer, Nuska; Hübner, Harald; Gmeiner, Peter; Prante, Olaf; Heinrich, Markus R.
Abstract Introduction of [18F]fluoride ion into the aromatic core of phenylazocarboxylic esters was achieved in only 30 seconds, with radiochemical yields of up to 95 % (85(±10) %). For labeling purposes, the resulting 18F‐substituted azoester can be further converted in radical‐arylation reactions to give biaryls, or in substitutions at its carbonyl unit to produce azocarboxamides.